Maternal Dietary Restriction During the Periconceptional Period in Normal-Weight or Obese Ewes Results in Adrenocortical Hypertrophy, an Up-Regulation of the JAK/STAT and Down-Regulation of the IGF1R Signaling Pathways in the Adrenal of the Postnatal Lamb - Zhang, Song (Endocrine Society, 2013)
Maternal dietary restriction during the periconceptional period results in an increase in adrenal growth and in the cortisol stress response in the offspring. The intraadrenal mechanisms that result in the programming of these changes are not clear. Activation of the IGF and the signal transducer and activator of transcription (STAT)/suppressors of cytokine signaling (SOCS) pathways regulate adrenal growth. We have used an embryo transfer model in sheep to investigate the impact of exposure to either dietary restriction in normal or obese mothers or to maternal obesity during the periconceptional period on adrenal growth and function in the offspring. We assessed the adrenal abundance of key signaling molecules in the IGF-I and Janus kinase/STAT/SOCS pathways including IGF-I receptor, IGF-II receptor, Akt, mammalian target of rapamycin, ribosomal protein S6, eukaryotic translation initiation factor 4E-binding protein 1, eukaryotic translation initiation factor 4E, STAT1, STAT3, STAT5, SOCS1, and SOCS3 in female and male postnatal lambs. Maternal dietary restriction in the periconceptional period resulted in the hypertrophy of the adrenocortical cells in the zona fasciculata-reticularis and an up-regulation in STAT1, phospho-STAT1, and phospho-STAT3 (Ser727) abundance and a down-regulation in IGF-I receptor, Akt, and phospho-Akt abundance in the adrenal cortex of the postnatal lamb. These studies highlight that weight loss around the time of conception, independent of the starting maternal body weight, results in the activation of the adrenal Janus kinase/STAT pathway and adrenocortical hypertrophy. Thus, signals of adversity around the time of conception have a long-term impact on the mechanisms that regulate adrenocortical growth.